Islamic Rationality on the Influence of Global Consumerism Culture - Ega Rusanti; Syarifuddin Syarifuddin; A. Syathir Sofyan; Muhammad Ridwan (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
The culture of consumerism has expanded globally. Basically, this ideology is a derivative of investment capitalism which gives rise to a spirit of consumption to form